EVALUASI SALURAN IRIGASI TERHADAP PENDISTRIBUSIAN AIR PADA JARINGAN IRIGASI DI D.I. KALI MASJID DESA POJA KECAMATAN GAPURA KABUPATEN SUMENEP - Yusriyana Haerani; Ach. Desmantri Rahmanto (Fakultas Teknik, Universitas Wiraraja, 2023)
Secondary irrigation canals in D.I. Kali Masjid Poja Village, Gapura District, Sumenep Regency on the irrigation network in the elevation or bottom height of the channel upstream is lower than downstream, this of course makes researchers want to analyze the irrigation channel. This study aims to determine the value of the flow discharge that occurs in the channel and also wants to know whether there is an influence of elevation on the flow rate so that it affects the distribution to the land area on the irrigation network.The method used is to collect measurement data in the field. The data that has been obtained in the field is analyzed, the analysis processed is the calculation of elevation, calculation of flow velocity, calculation of effective rainfall, calculation of reliable discharge, calculation of channel efficiency, clean water needs and technical rotation.Based on the results of the location survey and processing of secondary channel elevation measurement data, there is an elevation discrepancy that is not in accordance with the irrigation channel planning standards, and the mainstay discharge in the channel is 30 L/sec smaller than the planned discharge value and the efficiency value in the channel is 80% this is below the secondary line efficiency standard of 90%. It can be concluded that the Secondary Irrigation Channel in D.I. Kali Masjid Poja Village, Gapura District, Sumenep Regency is less effective in its function, namely as a distribution of water to the surrounding land area.